EFFECT EXPERIENCE, PROFESSIONAL AUDITOR INDEPENDENCE AND VIGILANCE AGAINST FRAUD DETECTION (Empirical Study On Regional Public Accounting Firm in Central Jakarta) - Yessie, Afly (Archives of Business Research, 2020)
Abstract This study aims to examine the effect of the auditor's experience, independence and professional vigilance on fraud detection. This research was conducted on auditors working in the Public Accountant Firm (KAP) of the Central Jakarta area registered with the Indonesian Institute of Certified Public Accountants (Certified) in 2019 using questionnaires. The results indicated resources that the auditor's experience and professional vigilance had a significant effect on fraud detection. While independence does not Significantly influence of fraud detection. Keywords: Experience, independence, auditor's professional vigilance, fraud detection